The Efficacy of Jing Wan Hong Ointment for Nerve Injury Diabetic Foot Ulcer and Its Mechanisms - Shumei Jin; Mixia Zhang; Yan Gao; Xuebin Zhang; Guangzhi Cui; Yanjun Zhang (Journal of Diabetes Research)
Jing Wan Hong ointment contains 30 kinds of Chinese herbs, with functions of activating blood circulation to disperse blood stasis, clearing heat, eliminating dampness, and reducing swelling by detoxification. Therefore, Jing Wan Hong ointment may facilitate the healing of ulcers. The aim of this study was to evaluate the efficacy and mechanisms of Jing Wan Hong ointment for healing diabetic foot ulceration in Wistar rats induced by streptozotocin and sciatic nerve damage. The results showed that Jing Wan Hong ointment had a marked effect on foot ulcers in diabetic rats induced by initial nerve injury. These effects were manifested by reducing the foot ulcer size and Wagner grade after seven days of treatment. The diabetic rats with foot ulcers were almost healed after 21 days of treatment. Moreover, the mechanisms of this effect seem to be dependent on increased expression of PDGF mRNA, but there was no influence on the expression of TGF-β, VEGF, and FLT-1 mRNA.